Case report: Tree branch penetrating injury into zone III of the neck. (November 2022) - Barsoom, Randa; Rendon, J. Jesus; Bar-Or, David; Palacio, Carlos H.
Abstract: Introduction: Penetrating trauma to the neck can result in severe morbidity and mortality. Location of the injury dictates the appropriate clinical management. Challenging traumatic injuries require resourceful treatment options. Case presentation: A complex traumatic case of a foreign body penetrating the neck, the parotid gland, disrupting the internal jugular vein, with the tip resting at the anterior aspect of the C1 ring is reported. In this case, the authors seek to describe the clinical management of a vascular injury that resulted from penetrating zone III of the neck. Discussion: Due to the complex and dense presence of various structures in the neck, injuries can be difficult to manage. Thus, an algorithm identifies management strategies that are based on the location of the injury, signs of vascular injury, identified injured structures and the hemodynamic stability of the patient. Balloon tamponade has been described in other organs of the body and might be a therapeutic option in patients were venous injuries are difficult to access. Conclusion: Penetrating neck injuries continue to result in significant morbidity and mortality. However, with appropriate and efficient evaluation and management, better outcomes are expected as demonstrated in this case. Highlights: Penetrating neck trauma can affect various structures, and precise tract localization is essential which may require interdisciplinary management. Penetrating neck injuries are evaluated with appropriate primary survey, with airway management as the first step. Balloon tamponade is an intervention used in different parts of the body and is reasonable in patients with venous injuries that are difficult to access.